2008
DOI: 10.3174/ajnr.a1377
|View full text |Cite
|
Sign up to set email alerts
|

Relative Cerebral Blood Volume Values to Differentiate High-Grade Glioma Recurrence from Posttreatment Radiation Effect: Direct Correlation between Image-Guided Tissue Histopathology and Localized Dynamic Susceptibility-Weighted Contrast-Enhanced Perfusion MR Imaging Measurements

Abstract: BACKGROUND AND PURPOSE:Differentiating tumor growth from posttreatment radiation effect (PTRE) remains a common problem in neuro-oncology practice. To our knowledge, useful threshold relative cerebral blood volume (rCBV) values that accurately distinguish the 2 entities do not exist. Our prospective study uses image-guided neuronavigation during surgical resection of MR imaging lesions to correlate directly specimen histopathology with localized dynamic susceptibility-weighted contrastenhanced perfusion MR ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
272
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(290 citation statements)
references
References 29 publications
6
272
1
4
Order By: Relevance
“…[1][2][3][4][5][6] These results could be explained by chemoradiotherapy possibly causing a high degree of tumor cell and endothelial cell killing, resulting in the acceleration of the radiation necrosis. 15,19 However, even in second-look surgery, differentiation between pseudoprogression and real tumor progression is very difficult because pseudoprogression can still involve residual infiltrated tumor cells, often leading to erroneous interpretation by the pathologist. Therefore, the diagnosis of pseudoprogression can be made on the basis of the combination of the clinical manifestations, radiologic findings, and pathologic findings by the multidisciplinary team approaches.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] These results could be explained by chemoradiotherapy possibly causing a high degree of tumor cell and endothelial cell killing, resulting in the acceleration of the radiation necrosis. 15,19 However, even in second-look surgery, differentiation between pseudoprogression and real tumor progression is very difficult because pseudoprogression can still involve residual infiltrated tumor cells, often leading to erroneous interpretation by the pathologist. Therefore, the diagnosis of pseudoprogression can be made on the basis of the combination of the clinical manifestations, radiologic findings, and pathologic findings by the multidisciplinary team approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies conclude that specific relative thresholds are helpful, with lesion-to-normal white matter rCBV ratio thresholds ranging from 1.2 to 2.0 for delineation of pseudoprogression (low rCBV) from recurrent disease (high rCBV) [35][36][37][38]. This is supported by studies in brain metastases demonstrating high reliability of detecting tumor progression (high rCBV) from radionecrosis (low rCBV) using a lesion to normal white matter rCBV ratio higher than 1.5-2.0 [39,40] and studies showing that rCBV can reliably differentiate radionecrosis from true progression in malignant gliomas [38,41]. A significant issue with this simple dichotomy of "true progression" and "pseudoprogression" is that in practice, when progressive enhancement is detected, tumor often coexists with treatment-related enhancement.…”
Section: Perfusion Mrimentioning
confidence: 99%
“…Previous DSC-MR studies showed that true progression had significantly higher relative BV (rBV) than pseudoprogression [34,35] and TIN [36,37]. Using PCT, true progression showed significantly higher values of rBF, rBV, and PS than TIN [38][39][40].…”
Section: Differentiation Of True Progression From Post-treatment Effectsmentioning
confidence: 99%